Case Report: A cluster of cases with rash associated with Chlamydia pneumoniae infection - Tianyi Wu; Gang Wang; Nannan Xu; Ke Xu; Gonghai Chen (Frontiers in Medicine, 2026)
We report a case of clustered rashes among teenagers associated by Chlamydia pneumoniae (CP) infection. Most patients only presented with rashes without significant fever or other respiratory tract symptoms. Metagenomic next-generation sequencing (mNGS) of blood samples identified the culprit - the nucleic acid sequence of CP was detected in the peripheral blood of the index case. The results of targeted next-generation sequencing (t-NGS) of throat swabs further supported the presence of CP. After antibiotic treatment, the patients’ conditions improved. In this case, we should have a systematic understanding of rashes and mucositis caused by respiratory tract infections to facilitate further diagnosis and treatment.